Exploring Levels of Financial Literacy among University of Zambia Final Year Students - Mwange, Austin (IJRDO - Journal of Business Management, 2017)
This paper explored the levels of knowledge of financial literacy among University of Zambia final year students. A questionnaire was administered to 172 pre-final graduates who were sampled systematically. SPSS version 22 was used to analyse the data. The results generally indicate that the level of financial literacy among University of Zambia final year students shows that they were well versed with the benefits of financial literacy. There levels of financial literacy were rather high because there were more students who had knowledge about financial literacy than those who did not know in the three domains, which were assessed, and these are: a) General personal finance knowledge; b) Your knowledge of savings and borrowing and investments and d) Exposure to financial and monetary issues. In terms of personal financial management practices there was no significant difference by gender in terms of holding an account across all types of accounts except for student account, which had a significant value p < 0.05 (Table 2). The conclusion is that the majority of students have knowledge of financial literacy. The level of financial literacy among students at the University of Zambia is above average and gender is not a factor regarding personal financial management practices in terms of holding an account across all types of accounts except for the student account, which was significant p < 0.05. The results are not generalizable to the wider population of University students and in order to allow such generalization, a study should be conducted using a larger sample and embracing all university students in the country. This paper describes a pioneer study on levels of financial literacy. This topic can be improved as the need for rigorous evaluation of financial literacy grows at the same speed as the creation of more complex financial products